(untitled) (Czech Journal of International Relations, 2000)
The author begins his essay by recalling the most significant landmarks and objectives of Czechoslovak foreign policy after 1989 when, following the breakup of the bipolar division of the world, it was able for the first time to be a policy of an independent and sovereign state. Czechoslovak foreign policy at that time was under no circumstances simply an improvisation or a temporary reaction to the problems and requirements of the given situation, even though because of the speed with which the previous totalitarian regime collapsed, it was at first unable to have a precise foreign political concept. Among the priorities of that time was a “return to Europe”, the demand for the total withdrawal of Soviet troops from the territory of Czechoslovakia, a decisive role to be played by the CSCE in creating a new European security system, incorporation in the North Atlantic Council for cooperation, the conclusion of a Treaty on Trade and on trade and economic cooperation between the Czechoslovak Federal Republic and the European Community and European (association) agreements, joining the activities of all major international finance and monetary organisations, the creation of the Visegrad group, a Central European agreement on free trade and so-called “big” bilateral agreements. The foreign policy of the newly emerged independent Czech Republic took up this orientation after 1993. This policy was based on the comprehensive foreign political concept, approved by the Chamber of Deputies in April l993. The successful incorporation of the Czech Republic in all major European and Trans-Atlantic security, political and economic structures remained priority number one. The same applied to incorporation in the world economy and in international trade relations. This naturally included the promotion of bilateral relations with all principal members, boosting regional cooperation in the Central European area as well as relations with neighbouring states. The current Czech foreign policy pursued by the social democratic government (e.g. after 1998) took up the fundamental orientation and concept of priorities of previous governments, both in its policy statement and in its own Concept of the Foreign Policy of the Czech Republic. In the security sphere, the new government succeeded in bringing one of the priorities to a successful conclusion – admission to NATO. Negotiations on the priority of priorities of Czech foreign policy, admission to the European Union, have entered the phase of decisive concrete talks. The Czech Republic hopes to become “a stable, fully equal and active member of the international community” by the 21st century.